E-Learing of Health Protocols Improving School-Age Children's Skills Facing Offline Learning - Kili Astarani; Fidiana Kurniawati (STIKes Patria Husada Blitar, 2022)
The surge in confirmed cases of Covid-19, especially in children aged 6-18 years, on March 3, 2021, showed 9.2% of children in Indonesia were exposed to Covid-19 virus. This makes the government advises the public to implement health protocols and have clean and healthy living behaviors, especially in terms of washing hands. This study aimed to analyze the effect of E-learning of Health Protocols on the Skills of School-Age Children Facing Offline Learning at Pelita Bangsa Elementary School, Surabaya. The design of the study used pre-experimental using one-group pre-test post-test design method. The population in this study was 59 students at Pelita Bangsa Elementary School in Surabaya. There were 59 school-age children met the inclusion criteria using the total sampling technique. The inclusion criteria in this study were children aged 7-12 years, children who came to school during data collection, and children who were willing to be examined. The instrument used a hand washing checklist sheet. The data analysis used Wilcoxon. Before being given E-Learning of Health Protocols the unskilled category in washing hands with soap with a total of 51 respondents (86.4%), there was a significant difference in hand washing skills between before health education with E-Learning Media and after health education with a significant value of 0.000 (p < 0.05). E-Learning of Health Protocols affects the skills of school-age children to face offline learning at Pelita Bangsa Elementary School Surabaya.